Plasma fluoroacetic acid concentrations: Symptoms, hematological, and biochemical characteristics in patients with fluoroacetic acid poisoning in the emergency department. (May 2020) - Liu, L; Li, F; Dong, Z; Dong, G; Xu, J; Liu, W; Wang, X; Hai, X; Yu, K
Fluoroacetic acid (FAcOH) was once a highly toxic rodenticide widely used in the world. In the past, studies on the toxicity of FAcOH have focused on animal experiments. The toxicity of FAcOH to humans and the changes of FAcOH in plasma have not been studied. Therefore, the present study aimed to describe the changes of plasma FAcOH concentrations, hematological, and biochemical characteristics in patients with FAcOH intoxication. According to clinical symptoms, 68 patients from the emergency department were divided into different groups: convulsion group, unconsciousness group, death group, and control groups. Plasma FAcOH concentrations, hematological, and biochemical parameters were investigated. Results demonstrated that patients in the convulsion group and the unconsciousness group had a significant increase ( p < 0.01) in the level of neuron-specific enolase (NSE), creatine kinase MB (CKMB), glucose (GLU), and white blood cell count (WBC) and a significant decrease ( p < 0.01) in serum potassium compared with the control group, respectively. Moreover, patients in the death group had a significant increase ( p < 0.01) in the level of NSE, CKMB, N -terminal pro-brain natriuretic peptide, GLU, and WBC and a significant decrease ( p < 0.01) in serum potassium and total calcium compared with the survival group. The concentrations of FAcOH in plasma in the convulsion group, the unconsciousness group, and the death group were 72.31 ± 42.29, 118.33 ± 55.41, and 163.78 ± 43.32 μg/mL, respectively. These changes and the plasma FAcOH concentrations may increase our understanding of the toxicity of FAcOH to humans and may help doctors to judge the clinical prognosis of patients with FAcOH intoxication.